2020
DOI: 10.1002/mabi.202000292
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Crosslinked Nanofibers of Poly(Vinyl Alcohol)/Carboxymethyl‐Kappa‐Carrageenan Produced by a Green Process

Abstract: This study presents a new type of biocompatible nanofiber based on poly(vinyl alcohol) (PVA) and carboxymethyl‐kappa‐carrageenan (CMKC) blends, produced with no generation of hazardous waste. The nanofibers are produced by electrospinning using PVA:CMKC blends with ratios of 1:0, 1:0.25, 1:0.4, 1:0.5, and 1:0.75 (w/w PVA:CMKC) in aqueous solution, followed by thermal crosslinking. The diameter of the fibers is in the nanometer scale and below 300 nm. Fourier transform infrared spectroscopy shows the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 72 publications
1
16
0
Order By: Relevance
“…Aqueous solutions of carrageenans are generally highly viscous and difficult to electrospin [ 90 ]. As a result, there are only a few reports in the literature describing carrageenan electrospun nanofibers.…”
Section: Seaweed-derived Biopolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Aqueous solutions of carrageenans are generally highly viscous and difficult to electrospin [ 90 ]. As a result, there are only a few reports in the literature describing carrageenan electrospun nanofibers.…”
Section: Seaweed-derived Biopolymersmentioning
confidence: 99%
“…It has been reported that carboxymethylation of κ-carrageenans, affording structural analogues of heparin, may improve their properties, lowering the solution viscosity and enhancing the antibacterial and anticoagulant activities [ 90 , 93 ]. Along these lines, Madruga et al (2020) investigated the development of carboxymethyl-κ-carrageenan/PVA electrospun nanofibers as a biomaterial for tissue engineering applications.…”
Section: Seaweed-derived Biopolymersmentioning
confidence: 99%
“…[126] PVA/GE/CS fibrous scaffolds prepared using water and acetic acid (with 9% w/v polymer) as a noncarcinogenic solvent system and crosslinked by glutaraldehyde (GA) vapor showed potential application for soft tissue engineering. The fibers showed no cytotoxicity to L929 mouse fibroblast cells, and SEM results demonstrated that Desired application References GE/CS (13% w/v) 10 cm/15-25 kV/0.6-1 mL h −1 TFE/water (100:0-50:50) Scaffold for skin, cartilage, and cornea tissue engineering [ 126] CS/PVA (15% w/w) (7:3/5:5) 25 cm/20 kV/1.5 mL h −1 Distilled water Biocompatibility and controlled drug release [ 127] PCL (13% w/v) CHI/SCHI (2% w/v -90/10) 10 cm/11 kV/0.4 mL h −1 FA/AA (3:1) 0.5% AA EDC/NHS cross-linking Scaffolds for cell proliferation and spreading [ 128] PCL (17% w/v) CS (2% w/v) 20 cm/12 kV/1.0 mL h −1 Chloroform/DMF (70:30) EDC/NHS cross-linking Scaffolds for cartilage tissue engineering [ 129] PVA (10% w/v) SA (4-10% w/v) PVA (5% w/v) CMKC (1.25-3% w/v) 15 cm/15 kV/1.0 mL h −1 Deionized water Thermal cross-linking Scaffolds to support cell differentiation [ 135] Wound dressings for wound healing [ 136] PVA (9% w/v) SA (0.9-2.7% w/v) 10 cm/15 kV/0.4 mL h −1 Deionized water GA cross-linking Scaffolds for neural tissue engineering [ 137] PCL (12.5% w/v) GE/CS (13% -85:15)…”
Section: Tissue Engineering Applicationsmentioning
confidence: 99%
“…The addition of a sulfated polymer to the fibers enhanced ADSC response to osteogenic differentiation signals, showing that sulfated polymers are great candidates for application in tissue engineering to support stem cells (Figure 4). [135] PVA/CMKC fibers also showed potential application as wound dressings for wound healing due to their increased procoagulant and antibacterial activities when compared to the pure PVA fibers. CMKC contributed to higher platelet adhesion and activation on the fibers, coagulation in contact with human whole blood, and bactericidal activity to Pseudomonas aeruginosa and Staphylococcus aureus bacteria.…”
Section: Tissue Engineering Applicationsmentioning
confidence: 99%
See 1 more Smart Citation